Les ingénieurs pédagogiques dans l’enseignement supérieur technologique : quelles transformations des identités et des pratiques en IUT à l’aune de la dimension professionnalisante des formations et de la réforme du BUT ? - Cécile Redondo; Romain Perrier; Magali Roumy Akue; Béatrice Drot-Delange; Anita Messaoui (Éducation et Socialisation)
Our article examines at how the professional identities and practices of pedagogical supports at French university institutes of technology are affected by the reform of the university bachelor of technology in the context of the competency-based approach that is becoming widespread at university. Through a questionnaire survey, we highlight a classic process in organizational sociology: a reform that opens up prospects of autonomy for a professional category, in this case the university institutes of technology’s in short higher education, extended by one year of training. Their professional identity, previously defined ‘from above’ and lacking recognition, finds opportunities for redefinition ‘from below’, mobilising classic dimensions of their activity revisited by the new context, which thus plays a revealing role.